Hardening Ni3Al via complex stacking faults and twinning boundary - Zhang, Z.; Fu, Q.; Wang, J.; Xiao, P.; Ke, F.; Lu, Chunsheng (2021)
© 2020 Elsevier B.V. Introducing nanoscale planar defects instead of adding alloying elements has been applied to improve the mechanical properties of materials. In this paper, we show that, from an atomistic perspective, hardness of nickel aluminide (Ni3Al) can be effectively enhanced by complex stacking faults and twinning boundary. The size effect of planar defects is induced by a competition between hardening because of regeneration of stacking faults and softening due to detwinning. The complex stacking faults have a better hardening effect than twinning boundaries with a spacing below 3.0 nm. These findings provide new insights into nanostructural design of aerospace materials with high hardness.